Anti-N-methyl-D-aspartate encephalitis – a case study of symptomatic progression. (August 2015) - Bowes, Emma; Levy, Florence; Lawson, John; Mandalis, Anna; Mohan, Adith; Shannon Weickert, Cynthia
Objective: To present the diagnosis course and sequelae of a case of anti-N-methyl-D-aspartate (NMDA) receptor encephalitis, drawing attention to early psychiatric symptoms. Method: The literature on anti-NMDA encephalitis is reviewed and possible psychopathological mechanisms discussed. Result: New onset psychoses, presenting with the combination of hallucinations, dyskinesias and seizures and progressing to catatonia should be referred to neurology for consideration of anti-NMDA receptor encephalitis. Conclusion: Early diagnosis is important for a favourable prognosis.